The Effect of E-Wallet and Financial Literacy on Consumptive Behaviour in College Students of Faculty of Economic and Business, Raja Ali Haji Maritime University - Bahril Wahda; Mareskha Tiara Fitri; Risma Rosita Sari; Nurul Yusyawiru (Yayasan Edukasi Cakrawala Nusantara, 2024)
The purpose of this study was to determine the effect of e-wallet and financial literacy on the consumptive behaviour of students of the Faculty of Economics and Maritime Business at Maritime Raja Ali Haji University (UMRAH). The population that is the focus of research is students of the Faculty of Economics and Maritime Business at UMRAH from class 2020 to 2023. The sampling method used is the Hair et al. method with the number of research indicators as many as 13 and the range used is 10, so the number of respondents is 132 people. Data collection was carried out through the use of questionnaires. This study is quantitative with data analysis using simple and multiple regression techniques. The results showed that: (1) The use of e-wallets significantly affects the consumptive behaviour of students of the Faculty of Economics and Business Maritime. (2) Financial literacy does not have a significant impact on the consumptive behaviour of students of the Faculty of Economics and Business Maritime UMRAH. (3) Together, e-wallet and financial literacy have a significant impact on the consumptive behaviour of students of the Faculty of Economics and Business Maritime UMRAH The coefficient of determination (R2) shows that e-wallet and financial literacy can explain 21.5% of the variation in consumptive behaviour, while the remaining 78.5% is influenced by other factors not examined in this study.